Protective face masks through centuries, from XVII century plague doctors to current health care professionals managing the COVID-19 pandemic - Conti, Andrea Alberto (Acta Biomedica Atenei Parmensis, 2020)
The adoption of items similar to face masks by human beings dates back to the remote past. With specific regard to the use of face protections for medical purposes, from the beginning of the XVII century onwards in Europe physicians in charge of curing patients with plague wore a complicated, and subsequently typical, costume. The face mask included eye sockets of glass and leather headdresses with long, pointed beaks. These beaks were filled with scented spices, aromatic substances and perfumes to filter out the plague and to mask "bad air", which was considered to be the vehicle of the disease. In the XVIII and XIX centuries a number of advances regarding personal protection devices in health care were achieved. In the course of the 1918 influenza pandemic (Spanish flu), health care professionals began to use face masks in a routine way to protect themselves and their patients. From the sixties (XX century) onwards, the explosion of health care technology has led to a continuous refinement in the study of individual protection devices, also because, even in the presence of an increasing number of powerful antimicrobial agents, infectious diseases have remained dominant during these last decades. It is not by chance, therefore, that one of the consequences of the 2020 ongoing COVID-19 pandemic should be the fact that face masks have become essential again both inside and outside health care environments. Even if more than a century has passed from Fluegge’s historical definition of bacteria-laden droplets, the role of certain medical-preventive achievements of the past, including the paradigmatic model of protective face masks, continues to remain pivotal in this third millennium.